(untitled) (Research, Society and Development, 2021)
Objectives: to know the challenges of Humanitude Care Methodology in assisting institutionalized elderly in times of pandemic. Methodology: descriptive, exploratory study with a qualitative approach with the participation of eight health professionals from different regions of Portugal, trained in HCM. Data were collected during the month of August 2020, through individual semi-structured interviews. A content analysis by Bardin (2016) was used. Results: the challenges identified were social and physical isolation, use of personal protective equipment (PPE), lack of health professionals specialized in HCM, fear of contaminating and being contaminated. Conclusion: a pandemic brought challenges to health professionals who take care of institutionalized elderly, highlighting the insecurity of ignorance, in the case of COVID-19. The HCM defines itself as an indispensable tool in elderly care, as it allows an international relationship and strengthens the bonds between the elderly and health professionals, including nursing.